Packaging Materials and Technologies for Improving Quality of Frozen Foods - Harnkarnsujarit, Nathdanai (Journal of Food Technology, Siam University, 2015)
Quality of frozen foods is influenced by various factors including freezing operation, storage temperature, food components and packaging systems. Packaging materials e.g. PE, nylon, PET, etc. and packaging atmosphere surrounded foods have key role on quality changes of frozen products. This paper aims to review utilization of packaging materials and technologies applied in frozen foods to improve and monitor quality of frozen products. The principles of phase transition in freezing process and glass transition which affect quality deterioration of frozen foods are explained. Migration of water, i.e. ice recrystallization and water loss from foods is the major problem found in all frozen products. Several biochemical reactions during frozen storage are limited, however, take place and are accelerated during thawing e.g. lipid and protein oxidation, enzymatic reaction and microbial activity leading to loss of quality and safety. Developed packaging technologies i.e. modified atmosphere packaging, edible film/coating, active and intelligent packaging utilization and consequence on frozen food qualities are discussed. The appropriate selection of packaging materials and operations can minimize changes and improve quality of frozen foods.